Highly Chemoselective Iridium Photoredox and Nickel Catalysis for the Cross‐Coupling of Primary Aryl Amines with Aryl Halides. (6th October 2016) - Oderinde, Martins S.; Jones, Natalie H.; Juneau, Antoine; Frenette, Mathieu; Aquila, Brian; Tentarelli, Sharon; Robbins, Daniel W.; Johannes, Jeffrey W.
Abstract: A visible‐light‐promoted iridium photoredox and nickel dual‐catalyzed cross‐coupling procedure for the formation C−N bonds has been developed. With this method, various aryl amines were chemoselectively cross‐coupled with electronically and sterically diverse aryl iodides and bromides to forge the corresponding C−N bonds, which are of high interest to the pharmaceutical industries. Aryl iodides were found to be a more efficient electrophilic coupling partner. The coupling reactions were carried out at room temperature without the rigorous exclusion of molecular oxygen, thus making this newly developed Ir‐photoredox/Ni dual‐catalyzed procedure very mild and operationally simple.